A Detailed Protocol for Formaldehyde‐Assisted Isolation of Regulatory Elements (FAIRE). Issue 1 (1st April 2013) - Simon, Jeremy M.; Giresi, Paul G.; Davis, Ian J.; Lieb, Jason D.
Abstract: Nucleosome displacement is a key event in the regulation of gene expression in the eukaryotic genome. This unit details an approach called Formaldehyde‐Assisted Isolation of Regulatory Elements (FAIRE) for isolating nucleosome‐depleted regions. FAIRE does not rely on the use of antibodies or enzymes, and has proven successful in most eukaryotic cells and tissues. The set of regulatory elements enriched by FAIRE is similar to those identified through DNase hypersensitivity. The enriched fragments can be detected by quantitative PCR, tiling DNA microarrays, or next‐generation sequencing. Although the signal‐to‐noise ratio is typically lower than that observed for DNase assays, FAIRE has high sample‐to‐sample reproducibility, requires very low amounts of input material, is inexpensive, is amenable to high‐throughput adaptations, and is a relatively simple procedure with a high rate of success, even for those without extensive experience in molecular biology protocols. Curr. Protoc. Mol. Biol . 102:21.26.1–21.26.15. © 2013 by John Wiley & Sons, Inc.